The Analysis of Students’ Conceptual Understanding and Motivation in Guided Inquiry Science Learning Model Assisted by Android Virtual Laboratory (Journal of Innovative Science Education, 2019)
This study aimed to: (1) examine the feasibility of android virtual laboratory application in motion of objects material. (2) examine the practicality of android virtual laboratory application in motion of objects material. (3) find out the effectiveness of students’ conceptual understanding and learning motivation after participating in learning process with the guided inquiry model. (4) find out the difference in students’ conceptual understanding and learning motivation after participating in the guided inquiry model assisted by the android virtual laboratory application . This study used a research and development (R&D) approach by adapting the Alessi and Trolip development models. The participants were 106 grade VIII students at SMP 1 Jepon. The research instruments were conceptual understanding tests, motivational questionnaires, and student response questionnaires. The hypothesis testing of the study was carried out by the Wilcoxon test, the Mann Whitney test, and Independent Simples test using the SPSS program. The results of the study revealed that: (1) The android virtual laboratory developed application was very feasible to be used with an average percentage of eligibility alpha test of 83.34% from media experts, 70.5% from material experts, and 92.9%, from the beta test. (2) Students’ responses to the use of android virtual laboratory application scored 27.32 % which means it was "practical" to be used for learning process in science subject. (3) The experimental class was more effective shown by the increase of students’ conceptual understanding and motivation seen from the gain value. (4) There was a significant difference in the average of the students’ conceptual understanding and motivation of in the experimental class with the control class.